Being Fluent with Information Technology - National Research Council (U.S.) Committee on Information Technology Literacy (National Academies Press, 1999)
Computers, communications, digital information, software-the constituents of the information age-are everywhere. Being computer literate, that is technically competent in two or three of today's software applications, is not enough anymore. Individuals who want to realize the potential value of information technology (IT) in their everyday lives need to be computer fluent -able to use IT effectively today and to adapt to changes tomorrow. Being Fluent with Information Technology sets the standard for what everyone should know about IT in order to use it effectively now and in the future. It explores three kinds of knowledge-intellectual capabilities, foundational concepts, and skills-that are essential for fluency with IT. The book presents detailed descriptions and examples of current skills and timeless concepts and capabilities, which will be useful to individuals who use IT and to the instructors who teach them.